MANAJEMEN SUMBER DAYA PENDIDIKAN ISLAM - Nurul Laily Nilam Rahmawati; Ari Abi Aufa (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to examine the educational philosophy of Ki Hajar Dewantara and its relevance to strengthening character education in the modern era. Ki Hajar Dewantara viewed education as a process of shaping the whole human being, encompassing cognitive, emotional, and moral dimensions—expressed through the unity of cipta (thought), rasa (feeling), karsa (will), and karya (action). Education, according to him, should not focus solely on intellectual development but also nurture noble character and moral values essential for social life. Through his well-known motto “Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani,” he emphasized the educator’s role as a role model, motivator, and supporter in the learning process. This approach aligns with the principles of character education, which stress the importance of attitude and ethical development. In the midst of globalization and technological advancement, Ki Hajar Dewantara’s thoughts remain highly relevant in addressing the moral crisis and character decline faced by the younger generation. This research uses a qualitative approach through literature review to explore the character values embedded in his philosophy and their implementation in the current education system. The findings indicate that character education based on Ki Hajar Dewantara’s philosophy can serve as a strong foundation for nurturing a generation with integrity, noble morals, and love for the nation.